Shipping Opinions Through Demostrations Which Cause Road - Putri Syakilah; Mohammad Amir Bin Wan Harun (Program Pascasarjana UIN Sumatera Utara Medan, 2019)
Expressing opinions in public is an act that is permitted and legally protected by law. In general, everyone has the right to freedom of opinion, assembly, and expression as regulated in Article 28E Paragraph (3) of the 1945 Constitution of the Republic of Indonesia. Furthermore, these rights are also regulated under Law Number 9 of 1998 concerning Freedom of Expression in Public and Law Number 2 of 2002 concerning the Indonesian National Police. Freedom of expression is a fundamental human right owned by every citizen and serves as an important element in the implementation of democracy in Indonesia. However, in practice, the exercise of expressing opinions through demonstrations often creates problems that may undermine democratic values themselves. Demonstrations occasionally develop into anarchic actions, including acts of violence, destruction of public facilities, disruption of public order, and traffic congestion that negatively affect surrounding communities. Such conditions may cause material and immaterial losses and create social unrest. This study aims to analyze the legal regulations governing demonstrations in Indonesia and examine law enforcement efforts against demonstrators who engage in anarchic behavior. The research uses a normative legal research method with statutory and conceptual approaches by analyzing relevant laws and legal literature. The findings indicate that although freedom of expression is constitutionally guaranteed, its implementation must remain within the limits established by law and respect public order, security, morality, and the rights of others. Therefore, effective law enforcement and increased public legal awareness are necessary to ensure that demonstrations remain peaceful, orderly, and consistent with democratic principles and the rule of law.